Influence of thermal gradient in vortex states of mesoscopic superconductors - Duarte, E. C. S. [UNESP]; Presotto, A. [UNESP]; Okimoto, D. [UNESP]; Sardella, E. [UNESP]; Zadorosny, R. [UNESP] (Iop Publishing Ltd, 2014)
In general, the studies of finite size effects in mesoscopic superconductors have been carried out in such a way that the temperature parameter is constant in the entire system. However, we could have situations where a real sample is near a heater source, as an example. In such situations, gradients of temperature are present. On the other hand, mesoscopic superconductors are interesting systems due to the fact that they present confinement effects which influence all the vortex dynamics. Thus, in this work we studied the influence of thermal gradients on the vortex dynamics in mesoscopic superconductors. For this purposes, we used the time dependent Ginzburg-Landau equations. The thermal gradients produce an asymmetric distribution of the currents around the system which, in turn, yield interesting vortex configurations and difficult the formation of giant vortices.